Sustainable experimentation in Chemistry Teaching: Batch Adsorption Technique with activated carbon from the endocarp of coconut in water treatment (Research, Society and Development, 2022)
Chemistry is generally viewed in a repulsive way by high school students. This problematic condition is the result of the various impasses generated by traditionalist methods that are being applied in schools, such as the lack of contextualization in the teaching of Natural Sciences. Therefore, this study aimed to develop experimental classes contextualized to the socio-scientific dimensions of Chemistry; as well as based on Environmental Education (EA) in a class of the 4th year of the Technical Course Integrated to High School of Controle Ambiental do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - IFPB, João Pessoa campus. In this sense, by mediation of a mixed approach (qualitative and quantitative), the research group presented to the students a low-cost process for improving water quality via Batch Adsorption with activated carbon from the endocarp of the coconut (biodegradable adsorbent material for the treatment of hard water). The activity was divided into three parts: i) Application of the Virtual Survey Questionnaire (VSQ); ii) Conducting experimental classes; iii) Application of the Final Virtual Questionnaire (FVQ). In this process, the students presented satisfactory considerations regarding the pedagogical intervention, showing that this practice was important for technical and citizen training. Thus, the research in question aims to enable the pedagogical community to acquire new skills and abilities regarding the work of the implementation of EE, involving Green Chemistry (GC) and the Sustainable Development Goals (SDGs), in the school menu.